The role of mobile phones in governance-driven technology exports in Sub-Saharan Africa - Simplice Asongu; Ndemaze Asongu (African Governance and Development Institute (AGDI), 2017)
This study assesses how the mobile phone influences governance to improve information and communication technology (ICT) exports in Sub-Saharan Africa with data from 2000-2012. The empirical evidence is based on Generalised Method of Moments and three main governance concepts are used, namely: (i) institutional (comprising the rule of law and corruption-control); (ii) political (involving political stability/no violence and voice & accountability) and (iii) economic (including regulation quality and government effectiveness) governance. The following findings are established. First, there are positive net effects on ICT goods exports from independent interactions between mobile phones and `political stability' `voice and accountability' and corruption-control. Second, significant net effects are not apparent from independent interactions between mobile phones and government effectiveness, regulation quality and the rule of law. Theoretical and practical implications are discussed.
Keywords: L59; L98; O10; O30; O55; 330; Knowledge economy; Development; Africa